Technological literacy: design and testing of an instrument to measure eighth-grade achievement in technology education - Castillo, Mauricio, author; De Miranda, Michael A., advisor; Folkestad, James E., advisor (Colorado State University. Libraries, 2007)
This study was focused on the design and testing of an assessment instrument to measure eighth-grade student achievement in the study of technology. The instrument measured the impact of instruction in technology education to determine if technology education instruction guided by the Standards for Technological Literacy (STL) can enhance students' technological literacy. The assessment instrument designed lo measure technology literacy was reviewed by panel of experts in the field to attain content validity and was pilot-tested before being administered to two groups of eighth-grade students (N=272). The study utilized a two-group post-test only design, a treatment group who had received instruction in technology education in the form a modular instructional delivery classroom and a control group who had not received any formal education in the study of technology. The results of study found that eighth-grade participants taking a technology class performed better (M=15.42, SD=5.42) than those who had no previous technology class exposure (M=14.07, SD=5.25). In comparing the means of the eighth-graders' post-test, there was a significant difference F (1, 270) = 4.40, p=.037, p<.05 detected by the instrument designed and tested in this study. The findings in this study suggest that standards-based modular instruction in technology education enhances students technological literacy-an imperative for success in a world that is increasingly dependent on a technologically literate society.
Keywords: achievement; assessment; cognition; eighth-grade; technology education; technology literacy; technology literacy test; educational evaluation; vocational education; educational tests and measurements